Studi Kasus: Koksidiosis Bentuk Intestinal dan Sekum Disertai Dugaan Infeksi Virus pada Ayam Broiler di Kecamatan Ungasan, Bali - Rindar Mentari Nusanti Putri; I Putu Cahyadi Putra; I Made Kardena; I Gusti Ketut Suarjana; I Nyoman Mantik Astawa (Jurnal Veteriner Nusantara, 2026)
Coccidiosis, Avian Influenza (AI), and Newcastle Disease (ND) are important diseases in broiler chickens that can cause economic losses. This case report aimed to identify the causative agents and describe the pathological changes in broiler chickens suspected of having coccidiosis accompanied by viral infection in the Ungasan District of Bali. The broiler chickens were approximately 25 days old and had bloody diarrhea. The examinations included anamnesis, epidemiological investigation, anatomical pathology, histopathology, parasitology, and bacteriology. Based on epidemiological data, morbidity was 0.7%, mortality was 0.2%, and the case fatality rate was 30% of the total population of 14,000 birds. Anatomical pathology and histopathological examinations revealed changes in almost all organs, indicating infection with the AI and/or ND virus. Necrosis, hemorrhage, inflammatory cell infiltration, and clusters of Eimeria spp. at various life stages were observed in the intestines and caecum. Qualitative and McMaster fecal examinations revealed the presence of Eimeria spp. oocysts at a rate of 132,700 oocysts/gram. Bacteriological examination identified the growth of Escherichia coli, but without any indication of secondary infection from bacteria because Escherichia coli is the normal flora of the intestine. Based on these examination results, it can be concluded that the chickens were infected with intestinal and cecal coccidiosis caused by Eimeria spp., accompanied by suspected ND and/or AI.